2009
DOI: 10.1111/j.1528-1167.2008.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CK‐MB mass and plasma brain‐type natriuretic peptide concentrations following convulsive seizures in children and adolescents: Possible evidence of subtle cardiac dysfunction

Abstract: Summary Purpose:  To evaluate the presence of myocardial injury during convulsive seizures in children and adolescents by determining serum concentrations of cardiac troponin I (cTnI), creatine kinase‐MB mass (CK‐MB mass), and plasma brain‐type natriuretic peptide (BNP). Methods:  Thirty‐one children (20 boys; mean age, 6.6 ± 5.34 years) with convulsive seizures and 50 healthy children were enrolled. Serum cTnI, CK‐MB mass, and plasma BNP concentrations were analyzed 12 h after the seizure and repeated 7 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
(46 reference statements)
0
31
0
1
Order By: Relevance
“…Transient myocardiac ischemia likely results from increased perfusion demand, ictal tachycardia, and hypoxemia . Subtle elevation of ischemic cardiac markers as CK-MB and braintype natriuretic peptide have been found in the postictal period in children with convulsive seizures, but no troponin elevation has been found in response to epileptic seizures in adult patients with no known coronary disease (Alehan et al, 2009;Woodruff et al, 2003). These findings may be the expression of mild and reversible ischemic changes without cardiac infarction.…”
Section: Ictal Cardiac Ischemiamentioning
confidence: 95%
“…Transient myocardiac ischemia likely results from increased perfusion demand, ictal tachycardia, and hypoxemia . Subtle elevation of ischemic cardiac markers as CK-MB and braintype natriuretic peptide have been found in the postictal period in children with convulsive seizures, but no troponin elevation has been found in response to epileptic seizures in adult patients with no known coronary disease (Alehan et al, 2009;Woodruff et al, 2003). These findings may be the expression of mild and reversible ischemic changes without cardiac infarction.…”
Section: Ictal Cardiac Ischemiamentioning
confidence: 95%
“…Seizure provokes an increase of sympathetic tone, which, in turn, may stimulate the release of proBNP from cardiomyocytes. The latter possibility was indirectly supported by the findings that both CK-MB and proBNP increase simultaneously following seizure 2. However, this explanation is further complicated because vasovagal syncope also activates sympathetic tone temporarily,15 which may increase proBNP according to the same assumption 11.…”
Section: Discussionmentioning
confidence: 89%
“…The duration of preceding symptom is usually short in cases of cardiogenic syncope like as seizure attack 1. To differentiate the two diseases clearly, some biomarkers favoring a seizure attack in blood or cerebrospinal fluid (CSF), have been proposed,26 but its clinical application has not made yet.…”
Section: Introductionmentioning
confidence: 99%
“…could show the presence of elevated brain-natriuretic peptide and creatine kinase in patients with seizures, the first evidence of subtle cardiac dysfunction in epilepsy patients. [21] However, previous studies failed to show significant increase in the serum levels of cardiac troponin as a marker of myocardial ischemia following seizures. [19212223] On the other hand, earlier studies using other markers reported a significant increase in brain-natriuretic peptide in the first postictal hour.…”
Section: Discussionmentioning
confidence: 99%